Connectivity of Striped Marlin From the Central North Pacific Ocean - Lam, Chi Hin; Tam, Clayward; Lutcavage, Molly E. (Frontiers in Marine Science, 2022)
Striped marlin, Kajikia audax, have been in overfished condition in the Western and Central North Pacific, and overfishing is still occurring, prompting an urgent need to devise conservation and management measures based on the best, current information on biology and ecology of this species. Despite conventional tagging efforts off Hawaii, striped marlin movements are not known across the broader Pacific, and little research has been conducted since 2005. To address this gap, 31 popup satellite archival tags (PSAT) were deployed on striped marlin (138-192 cm eye fork length) between 2016 and 2019 via the Hawaii-based longline fleet. To complement tagging efforts, 148 fin clips were also collected for genetic analyses during June-August 2017. Tag attachments ranged from 1-365 days (median = 74), where mechanical failures and non-reporting tags lowered expected data returns. Striped marlin tracks revealed extensive spatial use of the Central Pacific, spanning 15°S to 43°N and 122 to 170°W, showing diverse seasonal dispersal patterns and individual movements, and some coincided in time and space with known spawning grounds. Genetic profiles of 55 Hawaii-landed striped marlin were assigned to two genetic groups: Australia, New Zealand and Hawaii (n = 19), and Hawaii alone (n=36), suggesting the Hawaii-based longline fleet interacted with individuals from multiple populations. A year-long track confirmed migration between the Central North Pacific and Australia (>9,400 km), and combined with genetic results, is the first to document regional connectivity. By combining tools from conventional and electronic tags, biological sampling, and genomic techniques, a more holistic understanding emerges, suggesting that striped marlin should be collectively managed. Under global warming scenarios and changing pelagic ecosystems, integrative knowledge is critical for designing effective management strategies for rebuilding sustainable populations across the Pacific Ocean.